STRENGTHENING TEACHERS' UNDERSTANDING OF THE INDEPENDENT LEARNING CURRICULUM - Ida Bagus Nyoman Mantra; Lianda Dewi Sartika; Rulianto Rulianto; I Nengah Astawa; I Nyoman Suwandi (Sekolah Tinggi Pariwisata Mataram, 2022)
The Covid-19 pandemic period was a special condition that caused different learning drawbacks and learning losses in the achievement of student competencies. In addition to learning losses, many national and international studies state that Indonesia has also experienced a learning crisis for a long time. Therefore, it is necessary to change the curriculum so that educational institutions are able to improve the quality of education. This research was conducted to improve the understanding of teachers as participants in the independent learning curriculum training. This study found that teachers’ understanding increased significantly after being given training on the independent learning curriculum. The results of this study imply that intensive training is needed on the concept of implementing the independent learning curriculum so that teachers can carry out more effective learning.